2000
DOI: 10.1055/s-0037-1613863
|View full text |Cite
|
Sign up to set email alerts
|

HPA-1 and HPA-3 Polymorphisms of the Platelet Fibrinogen Receptor and Coronary Artery Disease and Myocardial Infarction

Abstract: SummaryPlatelet fibrinogen receptor (glycoprotein [GP] IIb/IIIa) plays a fundamental role in atherothrombosis. The human platelet antigen (HPA) -1 and the HPA-3 are the most extensively studied polymorphisms of GPIIIa and GPIIb, respectively. This study was designed to test, in a large population, the hypothesis that these polymorphisms represent a risk factor for the occurrence of coronary artery disease (CAD) and myocardial infarction (MI).Consecutive, angiographically examined patients with significant coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 25 publications
5
42
2
Order By: Relevance
“…Since the initial report of Weiss linking HPA-1b allele with myocardial infarction among young patients [19], a number of clinical studies demonstrated an association between HPA polymorphic variants and platelet hyperaggregation accompanying acute coronary syndromes [20][21][22], but with inconsistent findings [23][24][25]. These discrepancies may be explained by differences in selection of study subjects and study design, since the impact of single genetic factors on the risk of CAD may be higher when examined along with other additional inherited or acquired risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Since the initial report of Weiss linking HPA-1b allele with myocardial infarction among young patients [19], a number of clinical studies demonstrated an association between HPA polymorphic variants and platelet hyperaggregation accompanying acute coronary syndromes [20][21][22], but with inconsistent findings [23][24][25]. These discrepancies may be explained by differences in selection of study subjects and study design, since the impact of single genetic factors on the risk of CAD may be higher when examined along with other additional inherited or acquired risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…The studies to determine whether the HPA-3 a/b polymorphism might be associated with increased thrombotic risk are less, and some studies found that HPA-3b was associated with a higher thrombotic risk, 15,16 whereas others did not. 17,18 The association between ESRD as well as native AVF thrombosis and the HPA-3 a/b polymorphism has not been studied in the Chinese population. In this study, we examined the association of the HPA-3 a/b polymorphism in Chinese Han patients suffering from ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it appears that the Pro33 polymorphism of glycoprotein IIIa alters human platelet aggregation, adhesion, and secretion, perhaps through the mechanism of increased signaling and cytoskeletal changes, leading to stabilization of platelet-platelet and/or platelet-extracellular matrix interactions (236). Another variant that has been studied in the GPIIb-IIIa gene is the Ile843Ser polymorphism that has been shown to be associated with increased risk of MI in young women in the presence of other risk factors (247), but other studies have shown negative results (248,249).…”
Section: Genetic Variants In Platelet Surface Receptorsmentioning
confidence: 99%